Amiloidosis secundaria. Características clínicas. - LÓPEZ MARCELO, Fausto; VALDEZ Y., Guillermo; HERNÁNDEZ PACHECO, Javier; DELGADO, Wilson; M.H.V., LÓPEZ; N, SANTAYANA; SILVA DÍAZ, Homero (Revista Médica Herediana, 2013)
Objective: To determine the clinical characteristics of secundary amyloidosis. Material and methods: Retrospective study of 115 patients with histopatologic diagnosis of secundary amyloidosis since 1964 up to 1997, performed by renal (97.5%) or minor salival gland biopsy (2.5%).. Results: Conditioning diseases were tuberculosis (90.43%), bronchiectasis (6.08%) osteomielitis (1.74%). The clinical manifestations were edema in 98.2% of cases, proteinuria in 100%, hypotension in 30.43% and diahrrea in 33.91% of the patients. Proteinuria in 24 hour fluctuated between 1.26 gr. and 3.23 gr. The ranged in which serum albumin fluctuated was 0.6 to 3 gr/dl. Only 5% of patients had normal renal function and 95% renal insufficiency. ( Rev Med Hered 1999; 10:45-48 ).